Analysis of Biogas Power Plant Efficiency in Covered Lagoon Digester System - Para Atmaja, I Gede; Rumokoy, Stieven N. (Frontier Energy System and Power Engineering, 2020)
Palm oil mill liquid waste or often referred to as POME (Palm Oil Mill Efluent) was previously just left alone without any special treatment for the utilization of the energy contained in it. Along with the development of technology, liquid waste can be processed into useful energy sources. Wastewater treatment with a covered lagoon system is widely used in the palm oil industry. The result of wastewater treatment is biogas. Biogas is then used as biogas generator engine fuel to be used as electricity. The amount of electricity to be obtained is directly proportional to the amount of biogas produced. While the amount of biogas produced depends on the amount of POME and the content of COD (Chemical Oxygen Demand) in the POME. To see how effective the Biogas Power Plant Â has been built, it is necessary to calculate the efficiency of each treatment. From the results of calculations, the efficiency of wastewater treatment reaches 94.80%. The efficiency of using biogas to energy reaches 99.29%. The work efficiency of a power plant is 19.65%. With the maximum processing prediction simulation, the maximum capacity of the power plant can only reach 1.48MW.